DRAT That Fat Cat! - Patton, Julia (New York, NY : AV2 by Weigl, 2019)
Will a mischievous, messy cat win over the heart of orderly, quiet Cornelius, or will he need to look elsewhere for a forever home?
AV2 Fiction Readalong by Weigl brings you timeless tales of mystery, suspense, adventure, and the lessons learned while growing up. These celebrated childrens stories are sure to entertain and educate while captivating even the most reluctant readers. Log on to www.av2books.com, and enter the unique book code found on page 2 of this book to unlock an extra dimension to these beloved tales. Real actors will bring the story to life as you read along in your own book.
First published in 2016 by Albert Whitman & Company.
Keywords: Cats -- Juvenile fiction; Pets -- Juvenile fiction; Friendship -- Juvenile fiction